Polytrimethylene terephthalate and preparation method thereof

By introducing dihydrazide into the PTT resin to form dynamic hydrogen bonds, the problems of low elongation and tensile strength of PTT resin are solved, and the preparation of high-strength, high toughness and high ductility of polymer materials are achieved.

CN118812831BActive Publication Date: 2025-04-18GUANGDONG HENGTAN TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410909629.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2025-04-18
Estimated Expiration
2044-07-08

AI Technical Summary

Technical Problem

The existing PTT resins have low elongation and tensile strength, which are manifested as brittle fracture.

Method used

Polypropylene terephthalic acid or terephthalate, 1,3-propylene glycol and dihydrazide are used as raw materials to synthesize polypropylene terephthalate through esterification and acylation reactions, and the molar ratio is adjusted to introduce dynamic hydrogen bonds to improve intermolecular interactions and mechanical properties.

Benefits of technology

The elongation and tensile strength of PTT resins are significantly improved, and high-performance polymer materials with high strength, high toughness and high ductility are prepared.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004933186770000111
    Figure BDA0004933186770000111
  • Figure BDA0004933186770000121
    Figure BDA0004933186770000121
Patent Text Reader

Abstract

The present application belongs to the field of polymers, and discloses a poly(trimethylene terephthalate), which is obtained by esterification and acylation reaction of terephthalic acid or terephthalate, 1,3-propylene glycol, and dihydrazide as raw materials; wherein the molar ratio of terephthalic acid or terephthalate, 1,3-propylene glycol, and dihydrazide is: 0.4: 0.752-0.784: 0.016-0.048. The present invention uses terephthalic acid or terephthalate, 1,3-propylene glycol, and dihydrazide as raw materials to synthesize poly(trimethylene terephthalate), which has better elongation at break and tensile strength than poly(trimethylene terephthalate) synthesized by using aliphatic diamine as a modified raw material. At the same time, the present invention also provides a method for preparing poly(trimethylene terephthalate).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymers, and in particular to poly(trimethylene terephthalate) and a preparation method thereof. Background Art

[0002] As a commercialized aromatic polyester, PTT has excellent thermodynamic properties for synthetic fibers. PTT fibers have a softer feel and higher tensile resilience than polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) fibers; they have the softness of polyamide (PA) and better color; they have the fluffiness of acrylic (PAN) and stronger wear resistance. Therefore, PTT fibers are widely used in clothing fabrics, carpets, engineering plastics and other fields, becoming one of the hottest polymer materials in the world.

[0003] There are two methods for synthesizing PTT: transesterification and continuous esterification. Since the transesterification method will emit methanol, the main method for synthesizing PTT is the esterification method, which is the polycondensation of terephthalic acid and 1,3-propylene glycol. However, the existing commercial PTT has a low viscosity, a low glass transition temperature, and a low elongation at break, showing brittle fracture. Introducing an amide unit structure into PTT and promoting the formation of intermolecular hydrogen bonds can effectively improve the viscosity, crystallization properties, mechanical strength, etc. of PTT.

[0004] Marcel K mentioned that one way to enhance the performance of polyester is to introduce amide bonds into the main chain. Blending polyester and polyamide is a commonly used method of amide bond-modified polyester, which can achieve complementary advantages of polyester and polyamide. Retolaza A prepared a blend of polyamide 66 (PA66) and PET, which exhibited good mechanical properties. The "Yi Lun" product, which has been industrialized, is made by copolymerization of terephthalic acid, polyamide and ethylene glycol. The copolymer has good flexibility and easy dyeing. Hao Laidan and others used polycaprolactam prepolymer and ethylene terephthalate to prepare polyamide ester copolymers, and the fibers prepared from the product exhibited high mechanical properties.

[0005] CN109134850B discloses polyester amide and its preparation method and fiber made from the polyester amide. Polyester amide is obtained by esterification and acylation reaction of diol, terephthalic acid and / or its derivatives, diamine and / or its derivatives.

[0006] The maximum elongation at break of the product obtained by this solution is 130%.

[0007] CN108794741A discloses a polyester with random hybridization of amide structure and a preparation method thereof. The product is prepared from dicarboxylic acid monomer, diol monomer and diamine monomer, and has a maximum elongation at break of 107%.

[0008] As an alternative monomer to diamines, dihydrazide is generally used in the synthesis of polyurethane and is widely used in the preparation of adhesives and elastomers.

[0009] The use of dihydrazide in PTT resin is rare.

[0010] The technical problem solved in this case is: how to improve the elongation at break and tensile strength of PTT resin. Summary of the invention

[0011] The purpose of the present invention is to provide a poly(trimethylene terephthalate). The present invention adopts terephthalic acid or terephthalate, 1,3-propylene glycol and dihydrazide as raw materials to synthesize the poly(trimethylene terephthalate). Compared with the poly(trimethylene terephthalate) synthesized by adopting aliphatic diamine as a modified raw material, the elongation at break and the tensile strength of the poly(trimethylene terephthalate) are better.

[0012] At the same time, the invention also provides a method for preparing polytrimethylene terephthalate.

[0013] Unless otherwise specified in the present invention, nM represents nanomole / liter, μM represents micromole / liter, mM represents millimole / liter, and M represents mole / liter.

[0014] To achieve the above objectives, this application discloses:

[0015] A poly(trimethylene terephthalate) is obtained by esterification and acylation reaction of terephthalic acid or terephthalate, 1,3-propylene glycol and dihydrazide as raw materials;

[0016] The molar ratio of terephthalic acid or terephthalate, 1,3-propylene glycol and dihydrazide is 0.4: 0.752-0.784: 0.016-0.048.

[0017] Due to the synergistic effect of dynamic multiple hydrogen bonds, the introduction of dynamic hydrogen bonds (H bonds) can prepare high-performance polymer materials with high strength, high toughness and even high ductility. Compared with diamine monomers, hydrazide groups (-CO-NH-NH-) have multiple amino and hydroxyl units, so they can be added to the backbone or side groups of polyesters to improve the intermolecular interactions and mechanical properties with dense multiple hydrogen bonds.

[0018] In the above polytrimethylene terephthalate, the dihydrazide is one or more combinations of adipic acid dihydrazide, isophthalic acid dihydrazide, succinic acid dihydrazide and sebacic acid dihydrazide.

[0019] In the above polytrimethylene terephthalate, the terephthalate is dimethyl terephthalate or diethyl terephthalate.

[0020] In the above polytrimethylene terephthalate, the 1,3-propylene glycol is bio-based 1,3-propylene glycol.

[0021] At the same time, the present invention also discloses a method for preparing the polytrimethylene terephthalate as described above, comprising the following steps:

[0022] Step 1: Under the action of an esterification / transesterification catalyst, terephthalic acid or terephthalate, diol and diamine or dihydrazide undergo esterification / transesterification reaction to obtain a reaction system containing a prepolymer;

[0023] Step 2: Add a polycondensation catalyst and a heat stabilizer to the reaction system containing the prepolymer obtained in step 1, and perform a polycondensation reaction under reduced pressure. When the molecular weight of the product reaches the maximum, the polycondensation reaction ends to obtain polytrimethylene terephthalate.

[0024] In the above preparation method, the esterification / ester exchange catalyst and the polycondensation catalyst are independently selected from a mixture of one or more of n-butyl titanate, isopropyl titanate, tetraethyl titanate, zinc acetate, magnesium acetate, manganese acetate, antimony trioxide, and ethylene glycol antimony.

[0025] In the above preparation method, the heat stabilizer is one of trimethyl phosphate, triphenyl phosphite, Irganox1010, Irganox168 and Irganox245.

[0026] In the above preparation method, the esterification / ester exchange reaction temperature of step 1 is 180-240°C, and the esterification / ester exchange reaction time is 1-3h; the polycondensation reaction temperature of step 2 is 240-260°C, the polycondensation reaction vacuum is 10-100Pa, and the polycondensation reaction time is 2-3h.

[0027] In the above preparation method, the molar ratio of the esterification / ester exchange catalyst to terephthalic acid or terephthalic ester is 0.5-1.5:1000; the molar ratio of the polycondensation catalyst to terephthalic acid or terephthalic ester is 0.5-1.5:1000; the molar ratio of the heat stabilizer to terephthalic acid or terephthalic ester is 0.5-1.5:1000.

[0028] This application has at least the following beneficial effects:

[0029] (1) The reinforced and toughened PTT provided by the present invention solves the problems of low glass transition temperature and crystallinity of PTT and high rigidity of molecular segments, thereby preparing a bio-based PTT with high strength and good toughness.

[0030] (2) The reinforced and toughened PTT provided by the present invention has a simple preparation process, excellent thermodynamic properties, and related properties that are superior to existing commercial-grade PTT products, and can be industrially produced.

[0031] Specific embodiment

[0032] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. In the description of the present invention, it should be noted that, if no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0033] Example 1

[0034] (1) Add terephthalic acid (0.4 mol, 66.45 g), 1,3-propylene glycol (0.784 mol, 59.67 g), adipic acid dihydrazide (0.016 mol, 2.79 g) and tetrabutyl titanate (0.6 mmol, 0.20 g) into a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Introduce nitrogen into the kettle to replace the air in the kettle, pressurize to 2 bar, and heat to 230° C. at a stirring speed of 100 r / min for reaction for 1 h.

[0035] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, tetrabutyl titanate (0.6 mmol, 0.20 g) and trimethyl phosphate (0.6 mmol, 0.08 g) are added, and the mixture is stirred at a temperature of 240° C. and an appropriate stirring speed for 30 min.

[0036] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0037] Example 2

[0038] (1) Dimethyl terephthalate (0.4 mol, 77.67 g), 1,3-propylene glycol (0.768 mol, 58.44 g), adipic acid dihydrazide (0.032 mol, 5.57 g) and tetrabutyl titanate (0.4 mmol, 0.14 mg) were added to a 300 ml polymerization kettle, with an alcohol / acid ratio of 2. Nitrogen was introduced into the kettle to replace the air in the kettle, and then the pressure was increased to 2 bar. The temperature was raised to 230° C. at a stirring speed of 100 r / min and the reaction was carried out for 1 h.

[0039] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, tetrabutyl titanate (0.2 mmol, 0.07 g), zinc acetate (0.2 mmol, 0.04 g), and trimethyl phosphate (0.4 mmol, 0.06 g) are added, and the mixture is stirred at a temperature of 240° C. and an appropriate stirring speed for 30 min.

[0040] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0041] Example 3

[0042] (1) Add terephthalic acid (0.4 mol, 66.45 g), 1,3-propylene glycol (0.752 mol, 57.23 g), adipic acid dihydrazide (0.048 mol, 8.36 g) and isopropyl titanate (0.4 mmol, 0.11 g) into a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Introduce nitrogen into the kettle to replace the air in the kettle, pressurize to 2 bar, and heat to 230° C. at a stirring speed of 100 r / min for reaction for 1 h.

[0043] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, isopropyl titanate (0.4 mmol, 0.11 g) and trimethyl phosphate (0.4 mmol, 0.06 g) are added, and the mixture is stirred at a temperature of 240° C. and at an appropriate stirring speed for 30 min.

[0044] (3) After the reaction in step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0045] Example 4

[0046] (1) Dimethyl terephthalate (0.4 mol, 77.67 g), 1,3-propylene glycol (0.752 mol, 57.23 g), isophthalic acid dihydrazide (0.016 mol, 3.11 g) and isopropyl titanate (0.4 mmol, 0.11 g) were added to a 300 ml polymerization kettle, and the alcohol-acid ratio was 2. Nitrogen was introduced into the kettle to replace the air in the kettle, and the pressure was increased to 2 bar. The temperature was raised to 180°C at a stirring speed of 100 r / min and the reaction was carried out for 3 hours.

[0047] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, isopropyl titanate (0.4 mmol, 0.11 g) and trimethyl phosphate (0.4 mmol, 0.06 g) are added, and the mixture is stirred at a temperature of 240° C. and at an appropriate stirring speed for 30 min.

[0048] (3) After the reaction in step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 2 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0049] Example 5

[0050] (1) Add terephthalic acid (0.4 mol, 66.45 g), 1,3-propylene glycol (0.784 mol, 59.67 g), succinic acid dihydrazide (0.016 mol, 2.34 g) and tetrabutyl titanate (0.6 mmol, 0.20 g) into a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Introduce nitrogen into the kettle to replace the air in the kettle, pressurize to 2 bar, and heat to 240°C at a stirring speed of 100 r / min for reaction for 3 h.

[0051] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, tetrabutyl titanate (0.6 mmol, 0.20 g) and trimethyl phosphate (0.6 mmol, 0.08 g) are added, and the mixture is stirred at a temperature of 240° C. and an appropriate stirring speed for 30 min.

[0052] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 250°C for 2 hours to remove excess 1,3-propylene glycol and a small amount of oligomers to obtain reinforced and toughened PTT.

[0053] Comparative Example 1

[0054] (1) Add terephthalic acid (0.4 mol, 66.45 g), 1,3-propylene glycol (0.784 mol, 59.67 g), 1,6-hexanediamine (0.016 mol, 1.86 g) and tetrabutyl titanate (0.4 mmol, 0.14 g) into a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Introduce nitrogen into the kettle to replace the air in the kettle, pressurize to 2 bar, and heat to 230°C at a stirring speed of 100 r / min for reaction for 1 h.

[0055] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, tetrabutyl titanate (0.4 mmol, 0.14 g) and trimethyl phosphate (0.4 mmol, 0.06 g) are added, and the mixture is stirred at a temperature of 240° C. and at an appropriate stirring speed for uniform mixing.

[0056] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0057] Comparative Example 2

[0058] (1) Dimethyl terephthalate (0.4 mol, 77.67 g), 1,3-propylene glycol (0.768 mol, 58.44 g), 1,6-hexanediamine (0.032 mol, 3.72 g) and isopropyl titanate (0.4 mmol, 0.11 mg) were added to a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Nitrogen was introduced into the kettle to replace the air in the kettle, and the pressure was increased to 2 bar. The temperature was raised to 190°C with a stirring speed of 100 r / min, and the reaction was carried out for 1 h.

[0059] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, isopropyl titanate (0.4 mmol, 0.11 mg) and trimethyl phosphate (0.4 mmol, 0.06 g) are added, and the mixture is stirred at a temperature of 220° C. and at an appropriate stirring speed for uniform mixing.

[0060] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0061] Comparative Example 3

[0062] (1) Add terephthalic acid (0.4 mol, 66.45 g), 1,3-propylene glycol (0.752 mol, 57.23 g), 1,6-hexanediamine (0.048 mol, 5.58 g) and isopropyl titanate (0.4 mmol, 0.11 g) into a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Introduce nitrogen into the kettle to replace the air in the kettle, pressurize to 2 bar, and heat to 230° C. at a stirring speed of 100 r / min for reaction for 1 h.

[0063] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, isopropyl titanate (0.4 mmol, 0.11 g) and trimethyl phosphate (0.4 mmol, 0.06 g) are added, and the mixture is stirred at a temperature of 240° C. and at an appropriate stirring speed for uniform mixing.

[0064] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0065] Comparative Example 4

[0066] (1) Dimethyl terephthalate (0.4 mol, 77.67 g), 1,3-propylene glycol (0.736 mol, 56.01 g), 1,6-hexanediamine (0.064 mol, 7.44 g) and antimony trioxide (0.4 mmol, 0.12 mg) were added to a 300 ml polymerization kettle, and the alcohol-acid ratio was 2. Nitrogen was introduced into the kettle to replace the air in the kettle, and then the pressure was increased to 2 bar. The temperature was raised to 190°C at a stirring speed of 100 r / min and the reaction was carried out for 1 h.

[0067] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, antimony trioxide (0.4 mmol, 0.12 mg) and trimethyl phosphate (0.4 mmol, 0.06 g) are added, and the mixture is stirred at a temperature of 220° C. and at an appropriate stirring speed.

[0068] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0069] Comparative Example 5

[0070] (1) Add terephthalic acid (0.4 mol, 66.45 g), 1,3-propylene glycol (0.72 mol, 54.79 g), 1,6-hexanediamine (0.08 mol, 9.30 g) and tetrabutyl titanate (0.1 mmol, 0.03 g) into a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Introduce nitrogen into the kettle to replace the air in the kettle, pressurize to 2 bar, and heat to 230° C. at a stirring speed of 100 r / min for reaction for 1 h.

[0071] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, tetrabutyl titanate (0.1 mmol, 0.03 g) and trimethyl phosphate (0.1 mmol, 0.02 g) are added, and the mixture is stirred at a temperature of 240° C. and at an appropriate stirring speed for uniform mixing.

[0072] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened bio-based PTT.

[0073] Comparative Example 6

[0074] (1) Add terephthalic acid (0.4 mol, 66.45 g), 1,3-propylene glycol (0.784 mol, 59.66 g), 1,10-decanediamine (0.016 mol, 2.76 g) and tetrabutyl titanate (0.4 mmol, 0.14 g) into a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Nitrogen is introduced into the kettle to replace the air in the kettle, and then the pressure is increased to 2 bar. The temperature is raised to 230°C at a stirring speed of 100 r / min and the reaction is carried out for 1 h.

[0075] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, tetrabutyl titanate (0.4 mmol, 0.14 g) and trimethyl phosphate (0.4 mmol, 0.06 g) are added, and the mixture is stirred at a temperature of 240° C. and at an appropriate stirring speed for uniform mixing.

[0076] (3) After the reaction in step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0077] Comparative Example 7

[0078] (1) Add terephthalic acid (0.4 mol, 66.45 g), 1,3-propylene glycol (0.784 mol, 59.67 g), adipic acid dihydrazide (0.008 mol, 1.39 g) and tetrabutyl titanate (0.6 mmol, 0.20 g) into a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Introduce nitrogen into the kettle to replace the air in the kettle, pressurize to 2 bar, and heat to 230° C. at a stirring speed of 100 r / min for reaction for 1 h.

[0079] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, tetrabutyl titanate (0.6 mmol, 0.20 g) and trimethyl phosphate (0.6 mmol, 0.08 g) are added, and the mixture is stirred at a temperature of 240° C. and an appropriate stirring speed for 30 min.

[0080] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0081] Comparative Example 8

[0082] (1) Add terephthalic acid (0.4 mol, 66.45 g), 1,3-propylene glycol ((0.784 mol, 70.66 g)), adipic acid dihydrazide (0.08 mol, 13.9 g) and tetrabutyl titanate (0.6 mmol, 0.20 g) into a 300 ml polymerization kettle, with an alcohol-acid ratio of 2. Pass nitrogen into the kettle to replace the air in the kettle, pressurize to 2 bar, and heat to 240°C at a stirring speed of 100 r / min for reaction for 1 h.

[0083] (2) After the reaction in step (1) is completed, the pressure is adjusted to normal pressure, tetrabutyl titanate (0.6 mmol, 0.20 g) and trimethyl phosphate (0.6 mmol, 0.08 g) are added, and the mixture is stirred at a temperature of 240° C. and an appropriate stirring speed for 30 min.

[0084] (3) After step (2) is completed, the pressure in the reaction vessel is reduced to normal pressure. The temperature is slowly increased from 240°C to 260°C, and the pressure is slowly reduced to 30 Pa. The reaction is carried out at 260°C for 3 hours to remove excess 1,3-propylene glycol and a small amount of oligomers, thereby obtaining a reinforced and toughened PTT.

[0085] Performance Testing

[0086] Melting point test: The melting point of the polymer was tested using a PerkinElmer DSC4000 differential scanning calorimeter.

[0087] Crystallinity test: The polymer film obtained by hot pressing was placed on a D / max-2550VB wide-angle X-ray diffractometer (WAXD, Rigaku, Japan) for scanning. The incident wavelength was The scanning range is 2θ = 5-60°, and the crystallinity (X c ).

[0088] Tensile strength and elongation at break: According to GB / T 1040.2-2022, dumbbell-shaped specimens with a total length of 75 mm and a thickness of 2 ± 0.2 mm were obtained by injection molding. They were placed on a WDW 3020 universal tensile tester (Shanghai Sansi) for stretching at room temperature. The stretching rate was 10 mm / min, the initial distance between the clamps was 50 ± 2 mm, and the gauge length was 20 ± 0.5 mm.

[0089] The test results can be found in Table 1

[0090] Table 1 Test results

[0091]

[0092]

[0093] Result analysis:

[0094] It can be seen from the various embodiments and comparative examples 1-5 that the elongation at break of the dihydrazide as the raw material is generally stronger than that of the diamine; at the same time, in comparative examples 1-5, when the amount of the diamine varies within the range of 0.016 to 0.08 mol, the elongation at break is optimal at 0.048 mol; in embodiments 1-3 of the present invention and comparative examples 7 and 8, the effect of different amounts of dihydrazide on the performance is verified. From the perspective of elongation at break alone, when adipic acid dihydrazide reaches 0.032 mol, its elongation at break is maximized and the tensile strength is the highest.

[0095] The possible reason for the above results is that due to the synergistic effect of dynamic multiple hydrogen bonds, the introduction of dynamic hydrogen bonds (H bonds) can prepare high-performance polymer materials with both high strength and high toughness. The hydrazide group (-CO-NH-NH-) has multiple amino and hydroxyl units, so the hydrazide group has a better strengthening and toughening effect than diamine. At the same time, the introduction of excessive diamine and dihydrazide groups leads to the destruction of the regularity of the polymer chain segments, and the reduction of crystallinity and strength.

[0096] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, and it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A polytrimethylene terephthalate, characterized in that: It is obtained by esterification and acylation reaction of terephthalic acid or terephthalate, 1,3-propylene glycol and dihydrazide as raw materials; The molar ratio of terephthalic acid or terephthalate, 1,3-propylene glycol and dihydrazide is 0.4: 0.752-0.784: 0.016-0.

048.

2. The polytrimethylene terephthalate according to claim 1, characterized in that The dihydrazide is one or more combinations of adipic acid dihydrazide, isophthalic acid dihydrazide, succinic acid dihydrazide and sebacic acid dihydrazide.

3. The polytrimethylene terephthalate according to claim 1, characterized in that The terephthalate ester is dimethyl terephthalate or diethyl terephthalate.

4. The polytrimethylene terephthalate according to claim 1, characterized in that The 1,3-propylene glycol is bio-based 1,3-propylene glycol.

5. The method for preparing polytrimethylene terephthalate according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: Under the action of an esterification / transesterification catalyst, terephthalic acid or terephthalate, 1,3-propylene glycol and dihydrazide undergo an esterification / transesterification reaction to obtain a reaction system containing a prepolymer; Step 2: Add a polycondensation catalyst and a heat stabilizer to the reaction system containing the prepolymer obtained in step 1, and perform a polycondensation reaction under reduced pressure. When the molecular weight of the product reaches the maximum, the polycondensation reaction ends to obtain polytrimethylene terephthalate.

6. The preparation method according to claim 5, characterized in that: The esterification / ester exchange catalyst and the polycondensation catalyst are independently selected from a mixture of one or more of n-butyl titanate, isopropyl titanate, tetraethyl titanate, zinc acetate, magnesium acetate, manganese acetate, antimony trioxide, and ethylene glycol antimony.

7. The preparation method according to claim 5, characterized in that: The heat stabilizer is one of trimethyl phosphate, triphenyl phosphite, Irganox1010, Irganox168 and Irganox245.

8. The preparation method according to claim 5, characterized in that: The esterification / ester exchange reaction temperature of step 1 is 180~240°C, and the esterification / ester exchange reaction time is 1~3h; the polycondensation reaction temperature of step 2 is 240~260°C, the polycondensation reaction vacuum degree is 10~100Pa, and the polycondensation reaction time is 2~3h.

9. The preparation method according to claim 5, characterized in that: The molar ratio of the esterification / ester exchange catalyst to terephthalic acid or terephthalic acid ester is 0.5-1.5:1000; the molar ratio of the polycondensation catalyst to terephthalic acid or terephthalic acid ester is 0.5-1.5:1000; the molar ratio of the heat stabilizer to terephthalic acid or terephthalic acid ester is 0.5-1.5:1000.

Citation Information

Patent Citations

  • Polyester randomly hybridized by amide structure and preparation method of polyester

    CN108794741A

  • Polyesteramide, its preparation method, and fibers obtained from the polyesteramide

    CN109134850B

  • Method for producing conductive coating film, and conductive coating film

    CN106663504A

  • Alkyd resin, double-crosslinked alkyd acrylate dispersion comprising alkyd resin, and preparation method and application of alkyd resin

    CN111196873A